Postpartum Depression Among Arab Women in Israel: Comparing Traditional and Modernized Women in a Traditional Society (Asian Journal of Social Science Studies, 2026)
The objective of this study was to understand how Arab women in Israel experience one of the most significant transitions in their lives, pregnancy and childbirth, who have undergone transitions toward modernity in their traditional society. The study included questionnaire to determine whether each woman has more traditional or modernized tendencies within the traditional Arab society. The study included 202 women, After the women expressed their willingness to participate in the study, five sessions were held: Immediately after marriage – modernization questionnaire, During the last two months of pregnancy – EPDS questionnaire, During the final month of pregnancy – EPDS questionnaire, After on one month of the delivery- EPDS questionnaire and After six months of the delivery- EPDS questionnaire It clearly revealed a modernization trend among Arab women in Israel. This study found that 12% to 15% of the sample suffered from PPD. It showed that modern women suffered from more severe depression after delivery than their traditional peers did. Nearly all the women diagnosed with PPD were closer to the modern end of the spectrum. When symptoms were discovered in traditional women, the changes in their behavior appeared to be more of an overall conclusion of this study. This study emphasizes the need for intervention programs to support the changes that women in Arab society in Israel are undergoing. The findings enable the early detection of the population at risk for PPD.